Point-of-care blood tests during home visits by out-of-hours primary care clinicians; a mixed methods evaluation of a service improvement. Issue 1 (15th January 2020) - Hayward, Gail; Dixon, Sharon; Garland, Sophie; Glogowska, Margaret; Hunt, Helen; Lasserson, Daniel
Abstract : Objectives: We aimed to evaluate test usage and patient and clinician experience following the introduction of point-of-care (POC) blood tests into a primary care out-of-hours service. Design: A mixed methods service evaluation comprising quantitative records of the clinical contexts of tests taken and qualitative interviews with clinicians. Research permissions and governance were obtained for patient interviews. Setting: Out-of-hours primary care. Participants: All patients requiring home visits from the service during the implementation period. Interventions: The i-STAT POC blood test platform was introduced to two bases providing home visits for a period of 8 months. Venous blood samples were used and two cartridges were available. The CHEM8 cartridge measures sodium, potassium, chloride, total carbon dioxide (TCO2), anion gap, ionised calcium, glucose, urea, creatinine, haematocrit and haemoglobin. The CG4 cartridge measures lactate, pH, PaO2 and PCO2, TCO2, bicarbonate, base excess and oxygen saturation. Primary and secondary outcome measures: The proportion of home visits where tests were taken, the clinical contexts of those tests, the extent to which clinicians felt the tests had influenced their decisions, time taken to perform the test and problems encountered. Clinician and patient experiences of using POC tests. Results: i-STAT POC tests were infrequently used, with successful tests taken at just 47 contacts over 8 months of implementation. The patients interviewed felt that testing had been beneficial for their care. Clinician interviews suggested barriers to POC tests, including practical challenges, concerns about time, doubt over whether they would improve clinical decision making and concern about increased medicolegal risk. Suggestions for improving adoption included sharing learning, adopting a whole team approach and developing protocols for usage. Conclusions: POC tests were not successfully adopted by an out-of-hours home visiting service in Oxfordshire. While some clinicians felt they could not add value, in other cases they resulted in improved patient experience. Adoption could be promoted by improving technical, team and education factors.